Human-Centered Enablement for the Development of Chinese Opera: New Pathways for Inheriting Yiyang Opera in Jiangxi Province - Liu Jia (Journal of Roi Kaensarn Academi, 2024)
Yiyang Opera is one of the four major Chinese opera singing styles in ancient China. It once permeated forty-seven Chinese opera genres as a dominant form, but has gradually been replaced by Beijing Opera and Kunqu Opera, which have inherited and carried on the tradition more vigorously. Despite its storied reputation, Yiyang Opera now faces bottlenecks in its inheritance. With the development of modern society, there is an urgent need for scholars to rethink pathways for passing down Yiyang Opera. This paper takes a human-centered approach to explore new avenues for the future inheritance of Yiyang Opera. Firstly, it proposes that cultivating and protecting inheritors is crucial for the inheritance of Yiyang Opera. It suggests approaching this from both fostering mid-career and young inheritors, and protecting elderly inheritors. For younger generations, training through opera education, personal enhancement, master mentorship, and action learning could be implemented. For elderly inheritors, combining home-based elderly care with inheritance institutes could leverage their skills. Secondly, the paper discusses constructing inheritance systems for Yiyang Opera in universities, including talent training models, curriculum design, and after-school practical activities to bring Yiyang culture onto campuses. Thirdly, expanding the popular foundation of Yiyang Opera is also key. This could be achieved by developing private Yiyang troupes, building Yiyang rural culture, and creating new contemporary Yiyang works to spread its influence among the masses. By innovating inheritance pathways and tackling challenges in protecting and passing on Yiyang Opera, this ancient art form can be passed down through generations, providing valuable theoretical references for Chinese opera inheritance. With multidimensional perspectives on inheriting Yiyang Opera, this paper proposes many positive recommendations of significant referential value in promoting the cultural inheritance and innovation of Yiyang Opera.